The Influence of Organizational Culture on Employee Performance - Yeti Kuswati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study was motivated by the insignificant performance of employees at Municipal Waterworks (Perusahaan Daerah Air Minum, PDAM) in Majalengka Regency office. Their performance was considered to be insignificant due to the following indicators: (1) some employees were less responsible resulting poor performance in carrying out the task; (2) some employees lack discipline in carrying out tasks such as coming and leaving work not following the applicable regulations; (3) some employees carried out their tasks not following the applicable guidelines (resulting poor quality of work); (4) There were delays in reporting by employees. This study used descriptive and survey methods by processing and analyzing quantitative data through a parametric statistical approach. The calculation was conducted using the SPSS version 19 program. The parameters used were variable X which was organizational culture and variable Y which was employee performance. According to Robin, organizational culture includes innovation and risk placement, clear attention, outcome orientation, people orientation, team orientation, aggressiveness, and stability. Meanwhile, according to Moeherionon, employee performance includes effectiveness, efficiency, quality, timeliness, productivity, and safety. After analyzing the data and testing the hypothesis, the results indicated that the organizational culture in Majalengka PDAM office was categorized well with the respondents’ response of 3.45 and a standard deviation of 0.574. Meanwhile, the employee performance reached a good category with a respondents’ response of 3.49 and a standard deviation of 0.705. The correlation coefficient (r) between variable X and Y was 0.828 indicating the influence of organizational culture on service quality by 68.5%. Moreover, the results of the t-test (significant level) obtained a t-value of 15.683 with a t-table of 1.661. Thus, t-arithmetic was greater than the t-table. Therefore, H0 was rejected and H1 was accepted. In other words, there was a positive and significant influence between organizational cultures (X) on employee performance (Y).